Propuesta de Modelo de Gestión para el Departamento de Mantenimiento del Hospital de Trauma del Instituto Nacional de Seguros - Fallas-Cordero, Andrés (Instituto Tecnológico de Costa Rica, 2017)
This project was developed at the Trauma Hospital of the National Insurance Institute located at Uruca and consists of developing a maintenance management model proposal for the Maintenance Department. Currently the maintenance unit lacks a study of its management, therefore a diagnosis of maturity of the current state of the Department was developed, through the Venezuelan Standard COVENIN 2500-93 and the MES audit, these reflected in a quantitative and similar way the level of Department management. The results obtained were analyzed, and with a clear vision, were defined the existing gaps and expectations to find points of improvement and initiatives of the different areas studied. Regarding the development of the management model, it is built with reference to multiple sources consulted, taking into account the organizational objectives, and its construction seeks to adapt to the current departmental structure. To complement this model, the construction of tools that give added value and sustain the proposal was made in order to improve the current state of the Maintenance Department. As a value proposition of the model, a proposal of a balanced scorecard was developed to the Department that involves everything it requires and contains, in order to have a solid structure of indicators for the lack of them. A study of the current workload of the unit was then developed in order to find the need for human talent to meet the unit's goals annually. This tool goes hand in hand with the need to justify the requirement of new personnel by the person in charge of the Department. Finally, the conclusions obtained from the development of the project and timely recommendations found to provide to the Maintenance Department are presented.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Gestión; Cuadro de Mando Integral; Indicadores; Talento Humano; Mantenimiento; Research Subject Categories::TECHNOLOGY::Engineering mechanics